Analysis Of Bad Credit Settlement In Bangun Mandiri Saving And Loan Cooperative - Khaiyirah Rahmadani Lubis; Ripho Delzy Perkasa (Peneliti.net, 2023)
This study aims to analyze the settlement of bad loans in the savings and loan cooperative Bangun Mandiri. Bad credit is a problem that is often faced by a person's finances on savings and loans. The purpose of this savings and loan cooperative is to increase the amount of money borrowed and the profit will be even greater. In this study, the principles applied in the discipline of the Bangun Mandiri cooperative, safety and the principle of upholding high respect in the Bangun Mandiri savings and loan cooperative. Several factors in bad credit in payment, the salary is not included, the period of delay in payment. In responding to late payments by visiting customers. The research method used was by interviewing and surveying the savings and loan cooperative, the Bangun Mandiri cooperative.